Distribution and Geochemical Significance of Rearranged Hopanes in Jurassic Source Rocks and Related Oils in the Center of the Sichuan Basin, China - Lu, Xiaolin (ACS Omega, 2021)
[Image: see text] Gas chromatography-mass spectrometry (GC-MS) analysis has revealed extremely high abundances of rearranged hopanes in Jurassic source rocks and related crude oils in the center of the Sichuan Basin. The detected rearranged hopanes include 17α(H)-diahopanes (C(27)D and C(29–35)D), early-eluting rearranged hopanes (C(27)E and C(29–33)E), and 18α(H)-neohopanes (C(29)Ts and Ts). Both the 17α(H)-diahopanes and the early-eluting rearranged hopanes exhibit a distribution pattern similar to that of the 17α(H)-hopane series, with a predominance of the C(30) member and the presence of 22S and 22R epimers of hopanes in the extended series (>C(30)). The results of this study show that the relatively high abundance of rearranged hopanes in Jurassic source rocks in the study area is associated with their depositional environments and with clay-mediated acidic catalysis rather than, as was previously thought, thermal maturity. Shallow lacustrine facies with brackish water and a suboxic to weak reducing sedimentary environment have contributed to the enrichment of rearranged hopanes, and clay-mediated acidic catalysis may also have had a positive influence on their abundance. The distribution patterns of the diahopane series indicate that the oils from Jurassic reservoirs in the Gongshanmiao Oilfield are sourced from Jurassic source rocks. Rearranged hopanes are therefore considered to be effective biomarkers for oil-source correlation in the center of the Sichuan Basin.